Platelet glycoprotein VI‐dependent thrombus stabilization is essential for the intraportal engraftment of pancreatic islets. Issue 6 (19th November 2020) - Chen, Chunguang; Rawat, Divya; Samikannu, Balaji; Bender, Markus; Preissner, Klaus T.; Linn, Thomas
Abstract : Platelet activation and thrombus formation have been implicated to be detrimental for intraportal pancreatic islet transplants. The platelet‐specific collagen receptor glycoprotein VI (GPVI) plays a key role in thrombosis through cellular activation and the subsequent release of secondary mediators. In aggregometry and in a microfluidic dynamic assay system modeling flow in the portal vein, pancreatic islets promoted platelet aggregation and triggered thrombus formation, respectively. While platelet GPVI deficiency did not affect the initiation of these events, it was found to destabilize platelet aggregates and thrombi in this process. Interestingly, while no major difference was detected in early thrombus formation after intraportal islet transplantation, genetic GPVI deficiency or acute anti‐GPVI treatment led to an inferior graft survival and function in both syngeneic mouse islet transplantation and xenogeneic human islet transplantation models. These results demonstrate that platelet GPVI signaling is indispensable in stable thrombus formation induced by pancreatic islets. GPVI deficiency resulted in thrombus destabilization and inferior islet engraftment indicating that thrombus formation is necessary for a successful intraportal islet transplantation in which platelets are active modulators. Abstract : The inferior islet engraftment observed in a mouse model of glycoprotein VI deficiency, a disorder that destabilizes thrombus, suggests that normal function of platelets in thrombus formation is necessary for successful intraportal islet transplantation.